Prevalence and correlates of post-stroke anxiety in Changde, China during 2023 following the lifting of COVID-19 restrictions - Luo, Shangyu; Hong, Yunjun; Wen, Jun; Zhang, Xiaobo (Frontiers in Psychiatry, 2024)
Background Studies on post-stroke anxiety (PSA) following the lifting of COVID-19 restriction measures are currently lacking. We investigated the factors affecting PSA after full release of COVID-19 epidemic in China. Methods Patients with stroke admitted to the First People’s Hospital of Changde City from March 2023 to September 2023 participated in a questionnaire survey comprising a general demographic questionnaire, the Generalized Anxiety Scale-7. Additionally, data on the National Institutes of Health Stroke Scale, modified Rankin Scale, C-reactive protein (CRP), thyroid-stimulating hormone (TSH), homocysteine, TOAST classification, and the stroke site were collected, and the correlations between these indices and the mental health conditions of the patients were evaluated. Results Among 947 patients, the incidence of PSA was 14.57%.PSA was not linked to prior COVID-19 infection. This study found that Sleep duration (P=0.01), hyperlipidemia (P=0.01), migraine (P=0.02), and family history of stroke (P=0.01) were associated with PSA. Conclusions Our study found that the prevalence of PSA was 14.57%. In addition, sleep duration, hyperlipidemia, migraine and family history of stroke were independent risk factors for PSA following the lifting of COVID-19 restrictions.